Formation Pore Pressure Prediction and Application Based on Aacoustic Logging - QI Wenli; WU Huimei; LOU Yishan; ZHAI Xiaopeng; LIU Hong (Cejing jishu)
Formation pore pressure prediction is an important factor in the study of wellbore stability. Accurate prediction of pore pressure can avoid safety problems, such as overflow and blowout, thereby improving drilling efficiency, reducing environmental impact, and minimizing economic losses. Huazhuang block in Jiangsu oilfield is a newly discovered shale oil block, which caused many complex accidents such as overflow and collapse due to inaccurate prediction of pore pressure during the construction process. To increase the prediction precision of pore pressure in the Huazhuang block, the article applied the equivalent depth method, the Eaton method and the effective stress method to predict the pore pressure, and analyzed the prediction results. The results show that the maximum error of the prediction results of the equivalent depth method and the effective stress method exceeds 10%, which cannot satisfy the engineering damands, while the prediction error of the Eaton method is the smallest, with a maximum error of 4.77%. Therefore, the application of the Eaton method for predicting formation pore pressure is most effective in the Huazhuang block, and the prediction results can guide on-site operation, reduce the occurrence of complex accidents, and provide important technical support for the development of shale oil in this block.